KOMUNIKASI KESEHATAN MENTAL PADA MAHASISWA DAN PERAN MASYARAKAT MENANGGAPI KEGAWATDARURATAN ISU KESEHATAN MENTAL - doris, astri (Jurnal Ilmiah Cerebral Medika, 2025)
Currently, mental health is a grave issue. It garners significant emphasis, particularly in senior secondary school and postsecondary education, owing to the elevated prevalence of mental health illnesses among individuals in that age group. The insufficient consideration and understanding of mental health lead to a lack of sensitivity among individuals and society towards mental health issues well-being, as well as preventive measures implementation in decreasing its occurence. Currently, it has been observed that persons at this stage of life often lack information and understanding about the significance and potential risks of mental health issues, leading to a tendency to be closed off and insensitive towards their ozzwn mental well-being. They are unable to locate a secure environment for open discussion and a sanctuary to seek solace in their troubles, therefore they choose to retain them alone. This study employs an exploratory qualitative methodology with the objective of acquiring comprehensive insights into the topic under investigation. Ultimately, society plays a vital role in shaping norms, perceptions, and cooperation in addressing mental health disorders during adolescence. Therefore, it is imperative for all segments of society to actively participate in overcoming these challenges and creating a secure and reliable environment for students to openly discuss their mental health issues. or preexisting issues that potentially leading into mental health disorders.